Relative expression of γδ T-cell receptor gene families detected by RT-PCR and capillary electrophoresis - Tesarova, L; Koutna, I; Dvorakova, M; Klabusay, M (International journal of immunogenetics, 2012)
γδ T cells are intensively studied because their function in infection, allergy, autoimmune disease, cancer and post-transplant period is not yet fully understood. PCR-based techniques were established to study the γ variable (Vγ) and δ variable (Vδ) gene families. PCR product evaluation is routinely carried out by Southern blot analysis or the third complementarity-determining region spectratyping, but a fast and simple assessment of Vγ and Vδ gene family expression is missing. The aim of our study was to test capillary electrophoresis as a potential method for evaluating the composition of the γδ T-cell population. This report provides optimized PCR conditions for γδ T-cell receptor amplification. Further, it describes the utilization of capillary electrophoresis in the Agilent 2100 Bioanalyzer to evaluate the relative expression of Vγ and Vδ gene families after their amplification. An application of the methodology to peripheral blood mononuclear cell samples from patients during haemato-oncological treatment is shown. The described methodology is fast and simple to operate and is therefore suitable as a first screening of the γδ T-cell population composition in tissues of interest.
Keywords: T-Lymphocytes; Leukocytes, Mononuclear; Receptors, Antigen, T-Cell, gamma-delta; hematologické nádory; Male; Time Factors; multigenová rodina; leukocyty mononukleární; T-lymfocyty; Hematologic Neoplasms; Middle Aged; mužské pohlaví; receptory antigenů T-buněk gama-delta; studie případů a kontrol; elektroforéza kapilární; Adult; polymerázová řetězová reakce s reverzní transkripcí; Multigene Family; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; ženské pohlaví; Humans; časové faktory; lidé středního věku; Reverse Transcriptase Polymerase Chain Reaction; Oligonucleotide Array Sequence Analysis; dospělí; Electrophoresis, Capillary; Female; lidé; Case-Control Studies